Influence of flexibility in the execution of movements in rhythmic gymnastics (Acta Scientiarum. Health Sciences, 2015)
The aim of this study is to evaluate the relationship between flexibility and execution/validation of movements that are characteristic of the rhythmic gymnastics, using both kinematics and the code of points to assess the importance of this physical ability in the practices of this sport. The study has a descriptive exploratory nature, and it was carried out by choosing 20 gymnasts from two teams of rhythmic gymnastics from the state of Paraná. Kinematics was used to collect data by relating it to the plasticity of the gymnastics movements. There is an association between the high level of flexibility and the skill of the athletes, regardless their category. Therefore, this study may estimulate further research of its subject, and will contribute to highlight the importance of the flexibility training in rhythmic gymnastics.